2023
DOI: 10.1108/jaoc-08-2022-0123
|View full text |Cite
|
Sign up to set email alerts
|

Royal family board directors and the level of ESG disclosures in GCC listed firms

Abstract: Purpose This study aims to examine the role of royal family members’ board of directors, as a specific aspect of corporate governance, on the firm’s environmental, social and governance (ESG) disclosures. Many firms in the world enjoy special political connections, benefit from tax exemptions and favorable treatments that are largely responsible for their economic endurance and strong performance. Design/methodology/approach The authors collect data from Thomson Reuters database on Gulf Cooperation Council (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 105 publications
0
7
0
Order By: Relevance
“…The existence of a CSR committee will reduce information asymmetry for companies and stakeholders, because the CSR committee, although not significantly moderating, is still positive regarding environmental, social and governance performance. Thus, companies use CSR committees to create the impression that the CSR activities carried out by the company are operating in the right way to meet the expectations of environmental and social preservation of society, but not yet the return on company assets (Arayssi & Jizi, 2023). The findings of this research also show that in practice sustainability reporting in Indonesian energy sector companies has not met expectations regarding reporting of non-financial information.…”
Section: Discussionmentioning
confidence: 80%
“…The existence of a CSR committee will reduce information asymmetry for companies and stakeholders, because the CSR committee, although not significantly moderating, is still positive regarding environmental, social and governance performance. Thus, companies use CSR committees to create the impression that the CSR activities carried out by the company are operating in the right way to meet the expectations of environmental and social preservation of society, but not yet the return on company assets (Arayssi & Jizi, 2023). The findings of this research also show that in practice sustainability reporting in Indonesian energy sector companies has not met expectations regarding reporting of non-financial information.…”
Section: Discussionmentioning
confidence: 80%
“…Arayssi and Jizi (2023) found that royal family directors on GCC boards negotiate fewer ESG reporting in firms. Shalhoob and Hussainey (2023) found that SMEs in Saudi Arabia lack awareness of ESG practices and disclosures and, therefore, the extent of their importance to sustainability performance.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Thus, ESG disclosure has become a burning issue in the field of corporate financial reporting, and, hence, this paper attempts to explore the impact of ESG risk score on firm performance. Arayssi and Jizi (2023) found that royal family directors on GCC boards negotiate fewer ESG reporting in firms. Shalhoob and Hussainey (2023) found that SMEs in Saudi Arabia lack awareness of ESG practices and disclosures and, therefore, the extent of their importance to sustainability performance.…”
Section: Introductionmentioning
confidence: 99%
“…The total number of board meetings, firm size, leverage, board independent) to check the magnitude of impact on ESG REPORTING. Numerous studies have used these variables for firm performance, among them, (Arayssi & Jizi, 2023;Bilyay-Erdogan & Öztürkkal, 2023;Lewellyn & Muller-Kahle, 2023;Lin et al, 2023;Rahman et al, 2023;Rauf et al, 2021;. Finally, we incorporated year dummies to control for the possible influence of time, as well as industry dummies to account for the unique effect of industry.…”
Section: Control Variablesmentioning
confidence: 99%